2022
DOI: 10.21037/atm-22-2150
|View full text |Cite
|
Sign up to set email alerts
|

Function, quality-of-life and complications after sacrospinous ligament fixation using an antegrade reusable suturing device (ARSD-Ney) at 6 and 12 months: a retrospective cohort study

Abstract: Background: Pelvic organ prolapse (POP) is a common pathology in the female population. Sacrospinous ligament fixation (SSLF) is one of the traditional transvaginal procedures for POP and high sacrospinous ligament fixation (h-SSLF) optimizes it using an antegrade reusable suturing device (ARSD-Ney). Previous studies on h-SSLF have focused on the correction of anatomical positions, with less assessment of patients' function, quality of life and complications. In this study, we evaluated post-operative complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…This outcome may be related to the increased difficulty of transvaginal single-port laparoscopic surgery. The intraoperative blood loss of this study was 134.44 ± 111.21 ml, which was higher than the 92.3 ± 91.4 ml of 453 SSLF patients (74) and 86.80 ± 91.44 of 50 H-SSLF patients (76). This outcome may be related to factors such as increased surgical difficulty, small sample size, and initial surgery.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This outcome may be related to the increased difficulty of transvaginal single-port laparoscopic surgery. The intraoperative blood loss of this study was 134.44 ± 111.21 ml, which was higher than the 92.3 ± 91.4 ml of 453 SSLF patients (74) and 86.80 ± 91.44 of 50 H-SSLF patients (76). This outcome may be related to factors such as increased surgical difficulty, small sample size, and initial surgery.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, the data was derived from 18 patients, as shown in Tables 1, 2. The average operation duration was 192.78 ± 38.81 min, which was longer than the reported 92.3 ± 31.5 min of 453 patients with SSLF (74), longer than the 122.8 ± 36.1 min of 57 SSLF patients (75), and longer than the 86.04 ± 28.70 min of 50 patients with H-SSLF (76). This outcome may be related to the increased difficulty of transvaginal single-port laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Injury to the pudendal nerve and its branches, which surround the sacral plexus, can explain buttock pain. Following SSLF, a 10% rate was recorded by Ping Wang et al [22], but this number dropped to 0 at 6 and 12 months postoperatively. One incidence of persistent thigh pain was reported by Feiner et al and which gradually settled after 12 months [14].…”
Section: Discussionmentioning
confidence: 94%